(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
In the control systems, the compensators are widely used to improve system dynamics, characteristics of the open loop system and the stability. The degree of convergence of the output waveform for any compensator depends upon the proper selection and tuning of the compensator. The dynamic structure and the control properties of lead, lag and lead-lag compensators are presented in this work. A simple method based on the frequency domain is adopted to design the three different compensators. The parameters which have effect on each compensator performance were studied and explained how to choose them to achieve the optimal performance. The compensator algorithms are implemented with MATLAB simulation in order to control the DC motor motion. The results and the comparative analysis confirm the effectiveness of the proposed three compensators and improve the system response.